Rede de organizações de catadores no Estado do Espírito Santo : modelagem matemática para avaliação de cenários do problema de localização - Garcia, Marcus Camilo Dalvi (2016)
The Brazilian Policy on Solid Waste highlights the importance of pickers organizations in the integrated management of recyclable municipal solid waste, establishing priority in involvement in the selective collection and reverse logistics systems. However, only organizing in networks can achieve market efficiency to meet the recycling industry selling large volumes of materials. Thus, this study aims to define the location of transshipment and storage centrals of recyclable waste to a network pickers organizations in the Espírito Santo through a mathematical model of two-echelon Mixed Integer Linear Programming (MILP). To this end, the present study aimed to evaluate the effect of estimating generation strategy of recyclable solid waste, the effect of recyclable recovery goals proposed for the Brazilian Solid Waste Plan, as well as the effect trucks carrying capacity in the financial result of a reverse logistics network of recyclable waste. Thus, it was noted that the effect of waste generation estimation strategy can impact on a financial results of the logistics network in the order of 61%, which would result in a revenue gap of approximately R$ 58,000 per week. A recovery goal of recyclable fraction of 30% for 2035 reflected in a financial income of approximately R$ 467,000 per week. It was also noted that as from projections targets above 40% recovery in 2035, begins the protagonism of micro and small companies in the recyclable market (can reach 62% of companies traded waste in the proposed network) due the verification of large surpluses recycling companies. For cases analyzed, transport costs could reach 33% in relation to total costs for homogeneous fleet of sixteen-ton trucks. With regard to occupant load percentage, it was verified that ten-ton trucks and twenty one-ton trucks are suitable for smaller and larger generation of municipalities, respectively. In all scenarios, the financial result was positive, including scenarios which took into account the current situation, from R$ 4.8 to 44.1 million annually.